The Implementation of Da’wah Learning in Shaping the Religious Character of Students at SMP Alkarim Kotabumi - Ridho Hidayah; Wahyudi Hidayah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research aims to determine the implementation of da'wah learning in shaping the religious character of students at SMP Alkarim Kotabumi. This research uses a qualitative approach with the type of field research. Data collection techniques are carried out through observation, interviews and documentation involving teachers and students. The data obtained was analyzed using qualitative descriptive methods through the stages of data reduction, data presentation and drawing conclusions.The results of the research show that the implementation of da'wah learning at Alkarim Kotabumi Middle School is carried out through classroom learning activities, da'wah practices such as cults and lectures, as well as various religious activities at school. The learning methods used include lectures, discussions, practice and example.This implementation contributes to forming students' religious character, which is shown by increasing discipline in worship, politeness, responsibility and social concern for others.